Fascist Pigs : Technoscientific Organisms and the History of Fascism - Saraiva, Tiago (Book collections on Project MUSE., 2016)
How the breeding of new animals and plants was central to fascist regimes in Italy, Portugal, and Germany and to their imperial expansion.